Bibliometric patterns and indicators of research collaboration of Egyptian health scientists: 1980 - Shehatta, Ibrahim; Mahmood, Khalid (Malaysian Journal of Library and Information Science, 2017)
The present study examines Egyptian publications and research collaboration in health sciences using Thomson Reuters InCitesTM over the period of 1980-2014. Egypt, in clinical, pre-clinical and health, is ranked 44 among all countries according to the Web of Science documents (quantity) and total citations (quality). It is ranked at 40 and 55 respectively for international collaboration and the total number of highly cited papers. The total publications of Egyptian scientists in health sciences were 31 382, of which 27 693 articles were multi-authored, indicating a co-authorship ratio of 88 percent. It reveals that Egyptian scientists have a great tendency to collaborate. The collaborated papers show a greater citation impact, category normalized citation impact, and journal normalized citation impact and h-index compared to single authored papers. This reveals that the visibility and impact of co-authored papers are higher than that of single authored ones, as well as the visibility and impact of internationally co-authored publications are higher than the single authored or domestic papers. Egyptian scientists, in clinical, pre-clinical and health, had joint publications with their colleagues in 166 countries during the period under study. These countries were grouped according to geographic position, scientific capacity and economic development rate. The results show that Egypt’s main partners were USA, Saudi Arabia, Germany, England and Japan. In addition, Egyptian researchers mostly co-published with colleagues in Europe, scientifically advanced countries and high income countries. The findings could inform policy makers to develop research policies aiming to foster and support collaborations at all levels -researchers, institutions and countries.